2010
DOI: 10.4103/0301-4738.71679
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of preoperative high blood pressure in cataract surgery among hypertensive and normotensive patients

Abstract: Incidence of preoperative rise in blood pressure (BP) in cataract surgery among hypertensive and normotensive patients.Objective:To study the incidence of preoperative rise in BP in cataract surgery among normotensive individuals and hypertensive patients with historic good BP control in a population without other major chronic diseases.Settings:Ophthalmology Service of a University Hospital.Materials and Methods:A prospective study with 822 patients older than 40 years of age, with cataract surgery indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…[1][2][3] A perioperative rise in blood pressure (BP) has been noted during cataract surgery. [4][5][6][7][8] In fact, the guidelines from the American Academy of Ophthalmology suggest that BP monitoring should be performed during cataract surgery by personnel, other than the operating ophthalmologist, who is qualified to monitor and manage the patient's systemic status. 9,10 In addition to the intraoperative BP rise, intravitreal anti-VEGF injections have been demonstrated to increase the lifelong risk of cardiovascular and cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] A perioperative rise in blood pressure (BP) has been noted during cataract surgery. [4][5][6][7][8] In fact, the guidelines from the American Academy of Ophthalmology suggest that BP monitoring should be performed during cataract surgery by personnel, other than the operating ophthalmologist, who is qualified to monitor and manage the patient's systemic status. 9,10 In addition to the intraoperative BP rise, intravitreal anti-VEGF injections have been demonstrated to increase the lifelong risk of cardiovascular and cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…1 Hypertension is a comorbidity for half of patients undergoing cataract operations, and even if medically controlled these patients are already at risk of preoperative rises in blood pressure. 2 Similar studies investigating the blood pressure effects of intracameral adrenaline found no intraoperative fluctuations in blood pressure as compared to or as adjuncts to topical mydriatics. 3,4 The only existing literature regarding complications of I/C PE indicates that its use is not associated with any statistically significant changes in surgical outcomes, 5 although the study in question did not directly measure the circulatory effects.…”
Section: Commentmentioning
confidence: 85%
“…It has already been documented that SSRIs increase the risk of gastrointestinal bleeding 1 and intracranial hemorrhage. 2 de Abajo 3 summarizes the mechanism by which the SSRIs potentiate bleeding. Platelets cannot synthesize serotonin; rather, serotonin is stored in platelets and released by certain stimuli to induce vasoconstriction and platelet activation, and to enhance fibrin formation.…”
Section: Commentmentioning
confidence: 99%
“…Rodrigo et al found that the hypertensive patients with good BP control and without other major comorbidities present a larger incidence of preoperative rise in BP than normotensive individuals. 8 Good long term BP control should protect the patient from the risk of last minute cancellation because of high BP.…”
Section: Table 2types Of Surgery Performedmentioning
confidence: 99%